2022
DOI: 10.1002/vms3.983
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of 1050 dogs with respiratory symptoms in Japan (2005–2020)

Abstract: Background: Few studies have investigated the incidence of respiratory diseases based on anatomical sites or the relationship between breed and these diseases. Objective:The objective of this study was to investigate the prevalence of canine respiratory diseases among dogs in Japan, with relationship to the breed. Methods:We retrospectively reviewed the medical records of dogs with respiratory symptoms and calculated the odds ratio (OR) to evaluate the relationship between breed and disease.Results: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In this study, NP was most common in both the GM and GV, followed by NIR. This result is similar to those of previous reports, suggesting that these diseases are major nasal diseases in dogs [ 21 , 27 , 35 ]. However, SNA resulted in fewer cases than in previous reports, especially for GV [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, NP was most common in both the GM and GV, followed by NIR. This result is similar to those of previous reports, suggesting that these diseases are major nasal diseases in dogs [ 21 , 27 , 35 ]. However, SNA resulted in fewer cases than in previous reports, especially for GV [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, if a predictive model is not applied, the probabilities of NP and SNA are low. In addition, SNA is more likely to occur in large breeds, especially in retriever breeds [ 2 , 27 ]; however, breeds could not be included in the conditions because of the small number of cases with SNA in our study. Therefore, there is a possibility that improvement in diagnostic accuracy can be expected by considering these breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In limited documented cases, upper respiratory tract aspergillosis was reported in brachycephalic purebred cats (Barrs et al., 2015 ), and Abyssinian cats were found to be predisposed to Mycobacterium avium systemic infection, including lung involvement (Baral et al., 2006 ). A previous study investigated the prevalence of respiratory diseases and their relationship with breeds in Japan's dog population (Nakazawa et al., 2022 ) and significant associations between specific breeds and respiratory diseases were identified. Interestingly, certain breed predispositions identified in this study had not been found in previous studies.…”
Section: Introductionmentioning
confidence: 99%